2016
DOI: 10.1177/0301006616652053
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Perceived Dominance and Prestige of Women With and Without Cosmetics

Abstract: Women wearing cosmetics have been associated with a higher earning potential and higher status jobs. However, recent literature suggests that status can be accrued through two distinct routes: dominance and prestige (Henrich & Gil-White, 2001). In two experiments, we applied a standardized amount of cosmetics to female faces using computer software. We then asked participants to rate faces with and without cosmetics for various traits including attractiveness, dominance, and prestige. Men and women both rated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 62 publications
11
69
0
3
Order By: Relevance
“…This evidence from Study 3 that makeup is associated with maturity is also supported by other findings. Specifically, it is consistent with the observation that makeup increases ratings of perceived status (Mileva, Jones, Russell, & Little, 2016;Nash, Fieldman, Hussey, Leveque, & Pineau, 2006; and perceived sociosexuality (Batres et al, 2018;McKeachie, 1952;Mileva et al, 2016;Osborne, 1996), both of which are associated with maturity.…”
Section: Discussionsupporting
confidence: 86%
“…This evidence from Study 3 that makeup is associated with maturity is also supported by other findings. Specifically, it is consistent with the observation that makeup increases ratings of perceived status (Mileva, Jones, Russell, & Little, 2016;Nash, Fieldman, Hussey, Leveque, & Pineau, 2006; and perceived sociosexuality (Batres et al, 2018;McKeachie, 1952;Mileva et al, 2016;Osborne, 1996), both of which are associated with maturity.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with the quality-jealousy hypothesis, O'Connor and Feinberg (2012) found that Canadian women reported greater jealousy to scenarios in which their romantic partner was imagined interacting with relatively feminine women. These results are consistent with other work reporting that women perceive other women with more feminine face and body shapes to present greater intrasexual competition (Fink et al 2014) and that women wearing makeup that exaggerates feminine facial color patterns elicit greater jealousy (Mileva et al 2016). Feminine physical characteristics are thought to reflect good physical condition in women, but not men (see O'Connor and Feinberg 2012), which would explain why feminine physical characteristics in men do not elicit jealousy.…”
Section: Introductionsupporting
confidence: 89%
“…This extends Mileva and colleagues' work, by taking into account evidence that women wear more makeup than is optimally attractive (Jones et al, 2014), and that quantity of makeup alters perceptions of traits that may be important in a good leader, such as likeability, trustworthiness and competence (Etcoff et al, 2011). If, in general, makeup enhances perceived leadership ability, this would be consistent with prior work relating makeup to status (reviewed in Mileva et al, 2016). Alternately, if makeup weakens perceived leadership ability, we would extend prior work, which demonstrates that makeup enhances perceptions of traits related to dominance when competing for mates, by suggesting that these patterns of findings do not generalize to leadership roles where women compete for other resources.…”
Section: Introductionsupporting
confidence: 84%
“…Our findings develop work by Mileva and colleagues (2016) as our data suggest that their prior work, where women were afforded traits related to dominance when wearing makeup, is likely due to makeup enhancing their perceived effectiveness as a competitor for a male mate (i.e., attractive women; Vaillancourt, 2013) rather than perceptions of their ability to lead others. Although prior work associates makeup with social dominance (see Mileva et al, 2016), positive effects of makeup may be specific to certain roles within an organization, such as in service industry roles where attractiveness to clientele may be more important for eliciting prosocial responses (e.g., from customers via tipping; Jacob et al, 2009). Indeed, prior work suggests that makeup may have negative effects on judgements of performance depending on whether the position under evaluation is a stereotypically female occupation (Cox & Glick, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation